EXPERIMENTAL STUDY OF THE EFFECT OF WATER-REDUCING ADMIXTURE AND RECYCLED FINE AGGREGATE ON MECHANICAL PROPERTIES OF CONCRETE - Ikhtesham Ul Haq,; Engr. Dr. Zaheer Ahmed,; Engr. Dr. Naveed Anjum,; Muhammad Kashif,; Muhammad Saqib Khan,; Muhammad Usaid Ur Rehman,; Muhammad Sohaib Khan,; Muhammad Irshad, (Spectrum of Engineering Sciences, 2025)
The utilization of recycled fine aggregate (RFA) in concrete has gained significant attention due to its potential to reduce environmental impact and conserve natural resources. However, the incorporation of RFA often leads to a reduction in the mechanical properties of concrete. This study investigates the combined effect of water-reducing admixture (WRA) and RFA on the compressive and tensile strength of concrete. The experimental program involved the preparation of concrete mixtures with varying proportions of RFA (0%, 50%, 75%, and 100%) and after trail for different dosages of WRA (2%, 3%, and 4% by weight of cement) and WRAs give good workability by use of 4% of WRAs. Compressive and tensile strengths were evaluated at 28 days. The results indicate that the addition of WRA significantly improves the workability and mechanical properties of RFA concrete. The optimal combination of 75% RFAs and 4% WRAs yielded the highest compressive and tensile strengths, demonstrating the potential for sustainable concrete production without compromising performance.